Self – directed learning readiness in online learning: a conceptual review paper / Masliza Deraman - Deraman, Masliza; Deraman, Fauziah; Mod Arifin, Ahmad Izzat; Deraman, Nurul Asyikin (Akademi Pengajian Bahasa, 2021)
The evolution of internet – based technologies has impacted all aspects including education. Online learning is not alien anymore as many higher learning institutions used the technology – mediated learning to deliver the information. The major advantages of online learning are flexibility, lots of autonomy and freedom to learn. In order to ensure the success of online learning, it requires lot of self-discipline as well as self – directed learning. However, student’s self – directed learning activities are rarely monitored which required investigation whether students are in fact possessing the readiness to carry out those activities. Therefore, the purpose of this study is to describe the level of students’ self – directed learning and to examine the factors that lead to students’ self – directed learning readiness. In most studies, the level of students’ self – directed learning are low compared to other dimensions which including technology skills, technology usage, technology availability and computer and internet efficacy. There are also three factors that lead to students’ self – directed learning readiness which are self – efficacy, desired for learning and self – management. Higher learning institutions need to access their students’ level of readiness and focusing on the factors that lead to their readiness. A clear understanding of the students’ level of readiness of self – directed learning readiness would enable instructors to provide necessary support to guide students towards self-direction especially in online learning activities. Furthermore, mastering self – directed learning readiness will be one of the powerful factors in implementing online learning successfully.